1997
DOI: 10.1002/(sici)1097-4628(19970425)64:4<631::aid-app2>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of compression-molded thermoplastic starch materials from normal and high-amylose maize starches

Abstract: ABSTRACT:The structural and mechanical properties of compression-molded normal and high-amylose maize starches were studied as a function of processing water content and ageing time. Rubbery thermoplastic starches were produced by compression molding of four maize starches with differences in amylose content and amylopectin structure. Glycerol (30% on the basis of dry starch) and water (between 10 and 35% on the basis of total mass) were used as plasticizers. After processing, the amorphous thermoplastic starc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 14 publications
(22 reference statements)
2
56
0
Order By: Relevance
“…For the thermogram of non-cross-linked starch, the melting peak was lost in broad decomposition peak. 31 The results were in accordance with the results reported by Liu et al 32 and Kumar et al 33 On the other hand, after cross-linking, the much higher decomposition temperature could be due to the more compact molecular structure and stronger intermolecular forces attributed to additional intraand intermolecular bonds formed due to cross-linking. Stability in Water.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…For the thermogram of non-cross-linked starch, the melting peak was lost in broad decomposition peak. 31 The results were in accordance with the results reported by Liu et al 32 and Kumar et al 33 On the other hand, after cross-linking, the much higher decomposition temperature could be due to the more compact molecular structure and stronger intermolecular forces attributed to additional intraand intermolecular bonds formed due to cross-linking. Stability in Water.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…In this regard, the past decade has witnessed development and restructuring to convert starch into a thermoplastic material (Kirby and others 1993;Lourdin and others 1995;Spence and others 1995;Van Soest and Borger 1997;Sen and Bhattacharya 2000;Gomes and others 2001). Plastic formulations comprising corn-based starch (6% to 50%), to enhance the susceptibility of plastic products to biological degradation, have also been reported others 1980, 1987).…”
Section: Irradiation In the Development Of Starch-based Packagingmentioning
confidence: 99%
“…It has been reported that long linear glucans, like amylose molecules, tend to form more entanglements compared to highly branched amylopectin molecules. 15 Therefore, the long chained amylopectin starch used in the present study should act as a linear chain and have an influence on the chain entanglements development during extrusion. For bio-based materials it is of interest, from a techno-functional point of view, to explore a potato starch with amylopectin of longer chains length and decreased degree of branching as a good potential raw material for improved packaging materials.…”
Section: Introductionmentioning
confidence: 99%